2005
DOI: 10.1007/s11998-005-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the reciprocity law for coating photodegradation

Abstract: Accelerating the photodegradation of commercial polymeric materials has great practical importance in the weathering community. However, questions exist as to whether high radiant flux exposure results can be extrapolated to in-service exposure levels. Based on the reciprocity law, the photoresponse of a material is dependent only on the total energy to which the specimen is exposed, and is independent of the exposure time and the intensity of the radiation taken separately. An experiment to validate the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…chemistry, then the extent of the damage can be obtained directly from Monte Carlo results or the equations above. For example, the kinetics of yellowing often appear to largely follow simple first order kinetics (8-10) as do changes in infrared absorption (12). If the curves do not follow the simple curves above, then depending on the understanding available, a more detailed Monte Carlo simulation might be useful.…”
Section: Deterioration In Physical Propertiesmentioning
confidence: 99%
“…chemistry, then the extent of the damage can be obtained directly from Monte Carlo results or the equations above. For example, the kinetics of yellowing often appear to largely follow simple first order kinetics (8-10) as do changes in infrared absorption (12). If the curves do not follow the simple curves above, then depending on the understanding available, a more detailed Monte Carlo simulation might be useful.…”
Section: Deterioration In Physical Propertiesmentioning
confidence: 99%
“…This approach carries with it the assumption of reciprocity, that higher UV dosing over short periods will approximate lower UV levels for extended periods of time. Some sources have validated the reciprocity law for photodegradation testing (Chin et al 2005). Other sources have found that reciprocity does not apply at higher levels of irradiance (Delany and Makulec 1963).…”
Section: Photodegradation Testingmentioning
confidence: 99%
“…As with microorganism inactivation, it is likely that the response is nonlinear for very low doses and for very high doses, but this does not prevent accurate testing from being conducted in the mid-ranges of UV dose. Chin et al (2005) found that an acrylicmalamine coating exposed to UV irradiance levels of 36-322 W/m 2 between 290 and 400 nm caused chemical changes in the coating, including chain scission, oxidation, and mass loss.…”
Section: Photodegradation Testingmentioning
confidence: 99%
“…and check whether the material obeyed reciprocity. 18 Thus one can see how to use such an approach. The material variables included in the degradation rate parameter, k, also make it clear how simple acceleration factors (for calculating natural exposure lifetimes from accelerated exposures) are unlikely to apply across a broad range of materials.…”
Section: Unit Processesmentioning
confidence: 99%